Daur Al-Lugah Al-‘Arabiyyah fī Taṭbīqāti Aż-Żakā Al-Iṣṭinā’i li Taqaddumi-l Haḍārah Al-‘Ālamiyyah Al-Hadīṡah - Ipan Hidayat; Nurul Al Fudiah; Tatang Hidayat (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2023)
In Modern civilization, artificial intelligence is transforming rapidly until it reaches its important outputs. The purpose of this study is to examine the reasons for its civilization's progress based on the ancient Islamic civilization and to examine the uniqueness of the Arabic language for facilitating social communication and contributing to the prosperity of Islamic civilization, as well as its relationship to the tremendous advances in technological applications based on the arts and sciences founded by Muslim scholars. In their research, the two researchers used the qualitative approach and the desk and descriptive approach, as they analyzed the education book based on the collected data and information. As for the results of the research, artificial intelligence is the most important outcome of the Fourth Industrial Revolution due to its multiple uses in educational, medical, economic, military, and industrial applications, among others. In addition, the emergence of artificial intelligence and its development cannot be avoided by the contribution of the Arabic language, relying on the review and study of Muslim scholars’ theories as a basic reference. For instance, the books of Muslim scholars that were written in Arabic such as Al-Jabr and Al-Muqabbalah by Al-Khwarizmi were indeed enlightening for the development of technologies. Therefore, Arabic constitutes a bridge in the transition of the ancient world civilization to the modern era.